Teknik Soal-jawab Dalam Pengajaran Imam Abu Hanifah (M.150h/767m): Suatu Analisis Terhadap Kitab Al-'Alim Wa Al-Muta'allim - Mohd Anuar Mamat (Fakulti Pendidikan, UM, 2024)
Method and teaching techniques are an important element in the education process. They are closely related to the effort toward realizing quality education and effective teaching in classrooms. This article presents the questioning techniques employed by Abū Ḥanīfah in his teaching. The discussion is based on his great treatise, al-‘Ālim wa al-Muta‘allim and his teaching practice. This article found that six techniques were applied by Abū Ḥanīfah during his teaching. The techniques can be used as an effective guidance for teachers in applying the questioning method in the classroom. This study is also intended to introduce one of the greatest scholars and his legacy in the Islamic education tradition as an example in solving issues in contemporary Islamic educational pedagogy.